Relationship between Body Weight and Dry Matter Intake of Dry-off Cows with Birth Weight and Body Measurements of Calves - Desi Surya Permatasari; Dian Wahyu Harjanti; Rudy Hartanto (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The aim of this research was to find out and examine the relationship between dry matter intake (DMI) and body weight of dry-off cows on calf performance. This research was conducted at CV. Capita Farm and Rias farmers group in Getasan, Semarang Regency, Central Java. The research material was 26 cows and 26 calves that were born. This research was conducted observationally with the observed parameters were changes in the cow's body weight and consumption of DMI for 2 weeks before parturition with data collection every week, and also calf body weight and calf body measuremnets including body length, height and chest circumference at birth. The model of the relationship between parameters was tested with a simple regression test and t-test to determine differences in birth weight between male and female calves. The results showed that the weight of the parent body and the amount of dry-off DMI cow consumption at the end of dry periode did not correlate with calf body weight and calf body size. Calf body weight was influenced by gender with males having heavier weights than birth weight of female calves. Weight of male and female calf was 40.93 and 35.91 kg, respectively. In conclusion, the body weight of the dry-off cows and DMI of the dry-off cows could not be used to estimate the birth weight and body measureents of calves.